Upaya Pemerintah Indonesia Dalam Mempertahankan UMKM dan Pariwisata Di Era New Normal: The Indonesian Government's Efforts in Maintaining Micro, Small and Medium Enterprises and Tourism in the Era New Normal - Iko, Nugroho Kartiko Priyo Utomo (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2022)
The Covid-19 pandemic has had a major impact on many sectors of life. In Indonesia, almost all sectors of life. Starting from the economy, health, tourism, Small Medium Micro Business and others. In the tourism and Small Medium Micro Business sectors themselves, almost all activities in these sectors were completely paralyzed during the Covid-19 pandemic. This study aims to see how the government's efforts in maintaining the life of Small Medium Micro Business and tourism in Indonesia. So that the Small Medium Micro Business and Tourism sectors can stay alive and survive in the difficult times of the Covid-19 pandemic. The research method used in this study is a Qualitative Literature Study whose data sources are obtained from journals, articles, books, social media, and various literature reviews that have been reviewed and analyzed. The results of this study indicate that the government is highly committed to maintaining the Small Medium Micro Business and Tourism sector in Indonesia with various rules, assistance and facilities.